Hexane neem leaf extract more potent than ethanol extract against Aspergillus flavus - Jenny Hidayat; Ay Ly Margaret; Hanna Yolanda; Lies K. Wibisono (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUND Aspergillus flavus is one of the causes of aspergillosis, with a high virulence and resistance to standard antifungals, resulting in a high mortality rate. Medicinal plants are increasingly used as they are relatively safer with minimal side effects. Previously we found that the ethanol extract of neem (Azadirachta indica A Juss) leaves inhibits A. flavus growth in vitro. However, most chemical compounds with antifungal effect are nonpolar. The purpose of this research was to compare the antifungal effect of neem leaves extracted in a nonpolar solvent to that of leaves extracted in a polar solvent. METHODS An in vitro experimental research was conducted between October 2013 and January 2014. Neem leaves were extracted in ethanol or hexane at various concentrations. A macrodilution test with 48-hour incubation time was done in triplicate on 8 groups of samples. These comprised the neem leaf ethanol extract (NLEE) at 0.5, 1.0, and 2.0 g/dL, neem leaf hexane extract (NLHE) at 0.5, 1.0, and 2.0 g/dL, positive control, and negative control groups. Fungal growth was detected on Sabouroud dextrose agar. Statistical analysis used Chi square and Fisher’s exact test. RESULTS NLHE had a higher, but statistically non-significant, inhibitory effect on A. flavus than NLEE (p=0.996). At higher concentrations, the antifungal effect of NLHE is better than that of NLEE. CONCLUSION There is no significant difference in in-vitro inhibitory effectivity on A. flavus of neem leaves between extracts in polar and nonpolar solvents.